A multi-platform scaling study for an OpenMP parallelization of a discontinuous Galerkin ocean model. (31st August 2015) - Reuter, Balthasar; Aizinger, Vadym; Köstler, Harald
Abstract: We present a cross-platform scaling investigation for an OpenMP parallelization of UTBEST3D – a coastal and regional ocean code based on the discontinuous Galerkin finite element method. The study is conducted for a real life application on an unstructured computational mesh of the Northwest Atlantic with realistic topography and well resolved coast line on a broad selection of current computing platforms. Four numerical setups of increasing physical and computational complexity are used for comparison: barotropic with no vertical eddy viscosity, barotropic with an algebraic eddy viscosity parametrization, baroclinic with an algebraic eddy viscosity, and baroclinic with k – ∊ vertical turbulence closure. In addition to Intel Xeon and IBM Power6/PowerPC architectures, we also include Intel's new MIC processor Xeon Phi in the evaluation. Good scalability is found across all platforms with Intel Xeon CPUs producing the best runtime results and Xeon Phi demonstrating the best parallel efficiency.